Transcriptome characterisation and population genetics of Cunninghamia konishii Hayata – An endangered gymnosperm and implication for its conservation in Vietnam - Bich Hong Ha; Mai Phuong Pham; Quoc Khanh Nguyen; Thi Tuyet Xuan Bui; Giap Vu; Syed Noor Muhammad Shah; Dinh Duy Vu (Biodiversity Data Journal, 2025)
Biodiversity loss and degradation activities have a significant impact and devastating consequences on the ecosystem, eventually posing a major threat to many plant species, including Cunninghamia konishii. Deforestation and the growth of settlements are the main factors that affect the biodiversity hotspots in Vietnam such as Northwest, Northeast, North Central and Central Highlands regions. This has led to a decline of the species, so effective conservation strategies are urgently required. This study aimed to identify simple sequence repeat markers within expressed sequence tags from C. konishii, develop markers from them and assess the potential of those markers for diversity and population structure analysis of the plant. The Illumina HiSeq™ 4000 sequencing technology was applied for the transcriptomic analysis of C. konishii and genetic differentiation and population structure of C. konishii in Vietnam. In this study, the transcriptomes of C. konishii were analysed using the Illumina HiSeqTM 4000 sequencing system and a total of 5,361,856,500 base pairs were generated. De novo assembly indicated that 58,905 unigenes were generated (average length = 736.4 bp, N50 = 1,869 bp, Q20 = 98.44% and Q30 = 95.08%). A total of 23,232 and 16,510 unigenes had significant similarities amongst Nr and Swiss-Prot, respectively. In the GO database, 12,056 (20.47%) unigenes were annotated and these genes were divided into three major categories and 50 subcategories. In the KOG analysis, 13,248 (22.49 %) unigenes were annotated and divided into 25 gene function categories. In the KEGG analysis, 8,714 (14.79%) unigenes were annotated. According to the related pathways involved, they could be classified into 56 subclasses. In this study, we have identified a total of 2,854 EST-SSRs markers. Of the 960 primer pairs, 99 were validated and reported for polymorphism. The genetic diversity within and amongst C. konishii populations was studied using 10 SSR markers. A sample size of 96 trees considered from three distant populations in Vietnam was analysed in this study. Our data determined PIC = 0.67, Na = 4.05, Ne = 2.76 and P = 100%. We reported moderate levels of genetic diversity with Ho = 0.56 and He = 0.58 and the fixation index value was recorded as positive for three populations (XL, HSP and PH). The bottleneck tests showed clear evidence of a bottleneck in PH population sizes. Genetic differentiation amongst populations was recorded very low (FST = 0.029), indicating gene flow (Nm = 8.169). This result indicates gene exchange between the populations of ancient C. konishii from different geographical areas and regions. The analysis of molecular variance (AMOVA) showed that high genetic variation existed within individuals (90.68%) compared to amongst populations (2.97%). A Discriminant Analysis of Principal Components (DAPC) and Bayesian clustering grouped the populations into three genetically similar clusters. Additionally, candidate genes related to essential oil biosynthesis were identified. This study provides the first EST-SSR marker-based genetic diversity and population structure analysis of C. konishii, offering valuable insights for breeding and conservation efforts. The findings establish a key genetic resource for future conservation strategies with the aim of preserving this endangered species.